Constitutional Instruments for Human Rights and Minority Political Rights: Ensuring Equity and Inclusive Democratic Outcomes - Ayatullah Hadi; Muhammad Yazid Khofi; Azis Meinudin (Visi Pencerah Nusantara, 2026)
This study analyzes the role of constitutional instruments on human rights and minority politics in ensuring equity and producing inclusive democratic outcomes. Using a qualitative method with a Systematic Literature Review (SLR) approach, this study reviews publications from 2016 to 2025 obtained from the Dimensions and Scopus databases. Literature was selected based on criteria of academic quality, substantive relevance, and availability of full-text articles. The findings indicate that while constitutions provide a normative foundation for minority protection, their effectiveness is largely determined by the design of public policies and by institutions' capacity to eliminate structural barriers. The research findings confirm that the deficit in minority political rights is not only caused by discriminatory regulations but also by an exclusive concept of citizenship and institutional practices that perpetuate social hierarchies. Furthermore, the gap between anti-discrimination legal frameworks and the implementation of public services highlights the weakness of state mechanisms in ensuring equal access for vulnerable groups. This research contributes by offering an integrative understanding of the relationship between constitutional instruments, policy design, and democratic practices, and underscores the importance of